Identification, Validation, and Application of Molecular Diagnostics for Insecticide Resistance in Malaria Vectors. Issue 3 (March 2016) - Donnelly, Martin J.; Isaacs, Alison T.; Weetman, David
Abstract : Insecticide resistance is a major obstacle to control of Anopheles malaria mosquitoes in sub-Saharan Africa and requires an improved understanding of the underlying mechanisms. Efforts to discover resistance genes and DNA markers have been dominated by candidate gene and quantitative trait locus studies of laboratory strains, but with greater availability of genome sequences a shift toward field-based agnostic discovery is anticipated. Mechanisms evolve continually to produce elevated resistance yielding multiplicative diagnostic markers, co-screening of which can give high predictive value. With a shift toward prospective analyses, identification and screening of resistance marker panels will boost monitoring and programmatic decision making. Trends: Insecticide resistance in African Anopheles malaria vectors is a growing problem. Diagnosis and monitoring for insecticide resistance management would be aided by wider application of DNA markers. Protein-altering mutations in the conserved genes encoding insecticide target sites are often associated with insecticide resistance and are readily diagnosed. Emerging studies suggest that mutations accumulate in these genes and can act synergistically. Convergent results identify cytochrome P450s as crucial in metabolic resistance. Some of these genes confer resistance across multiple insecticides but few DNA markers are available. New genomic resources and functional validation approaches will shortly yield additional resistance-associated variants for monitoring and evaluation.